The firm - Waterfield, Robin, 1952- (Penguin readers. Level 5, Upper intermediate, 1999)
"Mitch McDeere is young, intelligent and ambitious. When he gets a job with the law firm of Bendini, Lambert & Locke it seems to be path to money and power. But soon Mitch finds that the firm is listening to all his phone calls, and the FBI want to speak to him. Money and power has a price -and it could be Mitch's life" --contratapa.